Identification and characterization of a plastidial phosphatidylglycerophosphate phosphatase in Arabidopsis thaliana. (7th January 2017) - Zhou, Yonghong; Hölzl, Georg; vom Dorp, Katharina; Peisker, Helga; Melzer, Michael; Frentzen, Margrit; Dörmann, Peter
Summary: Phosphatidylglycerol (PG) is the only phospholipid in the thylakoid membranes of chloroplasts of plants, and it is also found in extraplastidial membranes including mitochondria and the endoplasmic reticulum. Previous studies showed that lack of PG in the pgp1‐2 mutant of Arabidopsis deficient in phosphatidylglycerophosphate (PGP) synthase strongly affects thylakoid biogenesis and photosynthetic activity. In the present study, the gene encoding the enzyme for the second step of PG synthesis, PGP phosphatase, was isolated based on sequence similarity to the yeast GEP4 and Chlamydomonas PGPP1 genes. The Arabidopsis AtPGPP1 protein localizes to chloroplasts and harbors PGP phosphatase activity with alkaline pH optimum and divalent cation requirement. Arabidopsis pgpp1‐1 mutant plants contain reduced amounts of chlorophyll, but photosynthetic quantum yield remains unchanged. The absolute content of plastidial PG (34:4; total number of acyl carbons:number of double bonds) is reduced by about 1/3, demonstrating that AtPGPP1 is involved in the synthesis of plastidial PG. PGP 34:3, PGP 34:2 and PGP 34:1 lacking 16:1 accumulate in pgpp1‐1, indicating that the desaturation of 16:0 to 16:1 by the FAD4 desaturase in the chloroplasts only occurs after PGP dephosphorylation. Significance Statement: Phosphatidylglycerol (PG) is the only phospholipid in the thylakoid membranes of chloroplasts of plants. But the gene catalyzing the last step in PG synthesis was unknown. Here we identify the gene which encodes phosphatidylglycerolphosphate phosphatase.